Caring for people living with dementia and their informal caregivers: Current perspectives in Malaysia - Ken Joey Loh; Alvin Lai Oon Ng; Yook Chin Chia; Wan Ling Lee; Devi Mohan; Elil Renganathan (Malaysian Family Physician, 2024)
As dementia has been declared a global health crisis by the World Health Organization, this perspective paper aims to shed light on the current state of dementia care in Malaysia. The paper first outlines several barriers to dementia care in Malaysia. The shortage of geriatric specialists hampers the accessibility of dementia care and resources. There are also systemic barriers that hinder primary care physicians and family physicians from conducting early detection and providing more comprehensive dementia care. The lack of dementia-focused community services and public education further compounds issues for peopleliving with dementia (PLWD) and their informal caregivers (ICs). Consequently, ICs suffer mentally from caregiving demands, yet evidence-based psychosocial services to support them are scarce in Malaysia. This paper wraps up with recommendations aligning with Malaysia’s national plans and policies to prepare the nation for current and future dementia care needs.